2012
DOI: 10.3109/17482968.2011.626053
|View full text |Cite
|
Sign up to set email alerts
|

Formal ventilation patient education for ALS predicts real-life choices

Abstract: Our objective was to evaluate a single-session, hands-on education programme on mechanical ventilation for ALS patients and caregivers in terms of knowledge, change in affect and to determine whether ventilator decisions made after the education sessions predict those made later in life. Questionnaires were administered to 26 patients and 26 caregivers on four separate occasions. The questionnaires assessed knowledge of ventilatory support, feedback on the nature of the education programme, as well as self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
1
21
0
3
Order By: Relevance
“…Proactive team approaches have the potential to prevent crisis situations and costly interventions that may result from delays in decision-making. 31,34,76,77 However, the objective of a proactive, patient-centered, and collaborative multidisciplinary team is compromised by the impact of ALS on the patient and health system limitations. The challenge facing health professionals is how to bridge this gap.…”
Section: Discussionmentioning
confidence: 99%
“…Proactive team approaches have the potential to prevent crisis situations and costly interventions that may result from delays in decision-making. 31,34,76,77 However, the objective of a proactive, patient-centered, and collaborative multidisciplinary team is compromised by the impact of ALS on the patient and health system limitations. The challenge facing health professionals is how to bridge this gap.…”
Section: Discussionmentioning
confidence: 99%
“…This approach could introduce changes in stated preferences (or possibly stability of preferences) that would not be observed if stated preferences or real decisions were monitored longitudinally in real-world settings. The 1 study 14 in our review that evaluated trajectories of preferences under natural conditions found that the choices made by patients with amyotrophic lateral sclerosis to receive ventilatory support following an educational program on mechanical ventilation accurately predicted the clinical choices made by 76% of patients. The stability of preferences seemed to be greater among studies examining sicker populations (Figure 2), suggesting that for more seriously ill individuals, the questions may be more relevant, be contemplated more carefully, or may more closely respond to their current needs.…”
Section: Discussionmentioning
confidence: 99%
“…Against this background, patients make many decisions concerning symptom management and quality of life throughout the course of the disease. Decisions may include choices between invasive and noninvasive ventilation,79 insertion of gastrostomy to facilitate adequate nutrition and hydration,10,11 choices of mobility and communication equipment as independence decreases,12,13 completion of advance care plans anticipating future needs,14 involvement with home-based or inpatient palliative care services,15 and preferences for end-of-life care 16,17…”
Section: Introductionmentioning
confidence: 99%
“…Health professionals facilitate patient decision-making by providing decision-specific education,9,11,31 maintaining effective communication with patients and carers,17,24,26 and supporting patient autonomy 8. However, well-timed decision-making remains a challenge for health professionals and patients 17,37,38.…”
Section: Introductionmentioning
confidence: 99%